Analyzing social networks using R - Borgatti, Stephen; Agneessens, Filip; Everett, Martin; Johnson, Jeffrey (SAGE, 2022)
This approachable book introduces network research in R, walking you through every step of doing social network analysis. Drawing together research design, data collection and data analysis, it explains the core concepts of network analysis in a non-technical way. The book balances an easy to follow explanation of the theoretical and statistical foundations underpinning network analysis with practical guidance on key steps like data management, preparation and visualisation. With clarity and expert insight, it: Discusses a range of statistical models including QAP and ERGM, giving you the tools to approach different types of networks Provides a fully integrated discussion of digital data and networks like Twitter, sociolab and Amazon Offers digital resources like practice datasets and worked examples that help you get to grips with R software"--